BASES FOR QUANTUM ALGEBRAS AND SKEW POINCARÉ-BIRKHOFF-WITT EXTENSIONS (2017)
Considering quantum algebras and skew Poincaré-Birkhoff-Witt (PBW for short) extensions defined by a ring and a set of variables with relations between them, we are interesting in finding a criteria and some algorithms which allow us to decide whether an algebraic structure, defined by variables and relations between them, can be expressed as a skew PBW extension, so that the base of the structure is determined. Finally, we illustrate our treatment with examples concerning quantum physics.